Pengenalan Potensi dan Arah Peminatan Remaja - Arina Mufrihah; Iswatun Hasanah; Anna Aisa; Sri Rizqi Wahyuningrum (Jurnal Pengabdian Pada Masyarakat, 2021)
INTRODUCING POTENCY AND THE INTEREST PURPOSE TOWARDS ADOLESCENTS. Understanding towards potency and the interest purpose is essential for students because it will help them to plan their further education and future career development. However, especially specialization does not become the main concern in Lower Secondary Schools due to assumption that the students are far from career choice, whereas the future career decision is the result of understanding and exploration of potency and interest began from early adolescence. The methods used in this service program were divided into 4 steps: (1) survey session; (2) delivering material session; (3) assessment session; and (4) conclusion. This program succeeded helping students to understand their potencies, interest, kinds of interest, and the purpose of specialization which are crucial for their exploration of further education and career.